PENGARUH PARTISIPASI ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH DENGAN DESENTRALISASI, KOMITMEN ORGANISASI DAH GAYA KEPEMIMPINAN SEBAGAI VARIABEL MODERASI (Studi Empiris Pada OPD Kota Pekanbaru) - Putri Adinil Wulan; Darlis Edfan; L Azhar Al (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to examine the effect of budgetary participation on the performance of local government officials with decentralization, organizational commitment and leadership style as moderating variables. The population in this study was OPD in Pekanbaru City. In this study, the sample used was 96 respondents who were selected using purposive sampling method. This study uses primary data by distributing questionnaires. The analytical method used in this research is multiple linear regression analysis and moderated regression analysis. The analytical tool used in this research is Stastistical Product and Service Solution (SPSS) version 22.0. The results of this study indicate that: (1) Budget participation has a significant effect on the performance of local government officials with decentralization as a moderating variable with a significant value of 0.000 <(α) (0.05) and tcount (11.103)> ttable (1.98793) ( 2) Budget participation has a significant effect on the performance of local government officials with organizational commitment as a moderating variable with a significant value of 0.004 <(α) (0.05) and tcount (2.959)> t table (1.98793) (3) budget participation has a significant effect on the performance of local government officials with leadership style as a moderating variable with a significant value of 0.000 <(α) (0.05) and tcount (4.694)> t table (1.98793).Keywords: budgetary participation, decentralization, organizational commitment, leadership style and performance of local goversnment officials.